The Role of Ankle Brachial Index in Patient with Peripheral Arterial Disease; Diagnostic and Prognostic Tool - Haibi, Yaser Aamer Eisa Al-; Hussien, Abdulameer Muhsen (International Journal of Membrane Science and Technology, 2023)
Objectives: Peripheral arterial disease is an independent risk factor for developing major cardiovascular events, and even death; this makes its diagnosis important in early detection and prevention of these events. Ankle brachial index is a non-invasive, simple, bedside screening, diagnostic and even prognostic tool, patients with ABI less than 0.9 were found to have PAD, and at risk of cardiovascular events. Methods: A descriptive cross-sectional study of 338 patients was conducted during the period October 2021 to December 2022. They were referred to vascular and endovascular surgery unit at Ghazi Al-Hariri multispecialty teaching hospital/ Medical city teaching, they were presented with intermittent claudication and other PAD symptoms. Peripheral endovascular angioplasty was done; all were subjected to Ankle brachial index measurement. Results: The study involves 338 patients, among them males were 242 (72%), females were 96 (28%). Age ranged from 25-92 years old, with an age average of 61 years. A total of 203 (60%) were presented with classical lower limb claudication, 100 (30%) patients with atypical symptoms and only 35 (10%) patients with critical limb ischemia. A total of 216 (64%) patients with ABI between 0.4-0.9; 100 (29%) patients with ABI greater than 0.9; 19 (6%) patients with ABI less than 0.4, and only 3(1%) patients with ABI more than 1.4. Conclusion: Ankle brachial index is a useful, cost effective, simple non-invasive diagnostic tool in patients with peripheral arterial disease.